STRUKTUR KOMUNITAS MAKROZOOBENTOS SEBAGAI BIOINDIKATOR KUALITAS PERAIRAN ALIRAN SUNGAI RESUN, KABUPATEN LINGGA, KEPULAUAN RIAU - Kurnianto, Alief; Purnama, Aji; Dhamanda, Fariz; Al Haddad, Fatmah; Melani, Winny Retna; Zulfikar, Andi; Amelia, Karla; Nugraha, Tito Aria; Anzani, Yunita Magrima; Apriadi, Tri (Biospecies, 2026)
The Resun River is located in North Lingga Village, Lingga Regency, Riau Islands. Besides being a tourist attraction, the Resun River is also used by local communities for anthropogenic activities such as bathing and washing. The presence of macrozoobenthos can serve as an indicator in assessing river water quality. This research was conducted from July to September 2023 with the aim of determining the structure of the macrozoobenthos community and water quality status based on the presence of macrozoobenthos in the Resun River, Lingga Regency. Sampling locations were determined using a purposive sampling method, taking into account land use conditions and anthropogenic activities, with three sampling stations. The data analysis used was in the form of macrozoobenthos community structure and Family Biotic Index (FBI). Macrozoobenthos found in the Resun River consisted of 5 families. The predominance of Elmidae at Station 1 and 2 suggests highly oxygenated and relatively undisturbed environmental conditions. Conversely, the increased abundance of Chironomidae at Station 3 indicates greater anthropogenic influence, reflecting spatial variation in disturbance levels within the Resun River ecosystem. Based on the Family Biotic Index analysis, the water quality of the Resun River ranged from excellent to good, with FBI values of 3.34 – 4.57, indicating slight degradation of the aquatic ecosystem. The Resun River generally demonstrated favorable ecological conditions. Nonetheless, anthropogenic pressures observed near Station 3 merit further investigation, as they may contribute to increased inputs of organic pollutants into the aquatic system.